Case report: Rare abernethy malformation with hepatopulmonary syndrome in a pediatric patient - Ji, Lianfu; Ji, Zhaoming; Xiang, Dandan; Qin, Yuming; Yang, Shiwei (Frontiers in Pediatrics, 2022)
Abernethy malformation is a rare abnormality of the hepatic portal vein system with nonspecific and diverse clinical manifestations. Here we are describing a case of abernethy malformation with hepatopulmonary syndrome in a 10-year-old girl. Since 5 years ago, she suffered from persistent cough and slightly cyanosed lips. Cyanosed lips and mild digital clubbing in toes and fingers could be found during the physical examination. The results of auxiliary examinations suggested that her oxygen saturation fluctuated between 89-94% and the fasting blood ammonia was 98umol/L. Computer tomography angiography (CTA) showed the splenic vein joined the superior mesenteric vein and then flowed upward into the inferior vena cava directly. The same result was observed in delayed splenic arteriography. What is more，we found a tiny branch of intrahepatic portal vein through the inferior vena cava balloon occlusion test which could also show the confluence of the splenic vein and superior mesenteric vein with the inferior vena cava directly. From what has been discussed above, we come to a conclusion that the girl is a patient of type II abernethy malformation. Agiography is a sensitive and accurate method for the definitive diagnosis of abernethy malformation, it can also clarify the classification of disease which may be misdiagnosed by routine CT/MRI, because CT/MRI cannot detect tiny branches of intrahepatic portal vein.